AN INTERFERENCE-IMMUNE COMMUNICATION SYSTEM FOR DIGITAL DATA TRANSMISSION BASED ON A MULTI-CHANNEL CORRELATOR Part 1. DEVELOPMENT OF A SIGNAL FORMATION AND DECODING ALGORITHM FOR THE SUB-NOISE COMMUNICATION SYSTEM - A. V. Varavin; H. P. Yermak; D. P. Kudryavtsev; O. S. Vasiliev; M. V. Balaban; S. S. Melnyk; V. M. Zheltov; O. V. Fateev (Radio Physics and Radio Astronomy)
Subject and Purpose. The work aims to develop and study an interference-immune radio communication system for transmitting and receiving digital information and video images using a Software-Defined Radio (SDR).